Soldering flux, preparation method thereof and solder paste
By preparing a flux containing a specific proportion of components and mixing it with solder powder, the problem of excessive solder paste flux residue in the existing soldering technology is solved, and the stability of the solder joint is achieved and Improvement of photovoltaic performance.
Patent Information
- Application Number
- CN202411784107.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-07
AI Technical Summary
In the existing welding technology, the boiling points of the solvent and active agent in the flux of the solder paste are high, resulting in a large amount of residues produced after welding, affecting the stability of the solder joints and the performance of photovoltaic solar panels.
Provided is a flux containing 70-90% organic solvent, 2-10% rosin, 2-10% active agent, 0.50-2.50% corrosion inhibitor, and 2-10% thixotropic agent by specific mixing and grinding The process is prepared to form a volatile flux matrix and the solder paste is stirred with the solder powder.
The flux is easy to volatilize during welding, reducing residue after welding, improving the stability of the solder joint and photovoltaic absorption efficiency, and has a simple process and high welding efficiency.
Smart Images

Figure CN119387958A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of welding materials, and in particular to a soldering flux, a preparation method thereof and solder paste. Background Art
[0002] Solder paste, also known as solder paste or solder paste, is a semi-solid mixture commonly used in the electronic soldering process, mainly composed of solder and flux.
[0003] Flux is a chemical substance that can help and promote the welding process and has a protective effect. It mainly has the functions of removing oxides, reducing the surface tension of the material being welded, removing oil stains on the surface of the material being welded, increasing the welding area and preventing re-oxidation. These functions work together in the welding process to improve welding performance and enhance welding firmness.
[0004] Photovoltaic solar panels are devices that use the photoelectric effect to convert solar energy into electrical energy. The production process involves multiple links, including silicon wafer cutting, cleaning, coating, printing, welding, etc. Among them, the welding link is crucial to the performance and quality of solar panels, and solder paste plays an important role in this link.
[0005] The solder paste used in the existing welding technology has a high boiling point of the solvent, activator and other components in the flux, which are not easy to volatilize during the welding process, so a large amount of residue will be produced after welding. These residues will form protrusions and produce stress, and may also cause corrosion to the solder joints, causing the solder joints to detach or break, resulting in failure. The existing technology for welding photovoltaic solar panels generally uses copper wire and flux. Although this method has solvents, activators and other components that are easy to volatilize during the welding process and less residue after welding, this method is less efficient. There is also a technology that uses a method of filling gas in the solder paste. The gas is easy to volatilize during the welding process, thereby reducing the residue after welding, but this method is more complicated. Summary of the invention
[0006] In order to overcome the problems of the prior art, the solder paste used in the prior art has high boiling points of components such as solvents and activators in the flux, which are not easy to volatilize during the welding process, thus producing a large amount of residues after welding. These residues will form bulges and produce stress, and may also cause corrosion to the solder joints, causing the solder joints to detach or break, leading to failure. The prior art of photovoltaic solar panel welding generally uses copper wire and flux. Although this method has components such as solvents and activators that are easy to volatilize during the welding process and less residue after welding, this method is less efficient. There is also a technology that uses a method of filling gas in the solder paste. The gas is easy to volatilize during the welding process, thereby reducing the residue after welding, but this method has the disadvantage of a more complicated process.
[0007] First aspect
[0008] The invention provides a soldering flux, which comprises, by mass percentage, 70-90% of an organic solvent, 2-10% of rosin, 2-10% of an activator, 0.50-2.50% of a corrosion inhibitor and 2-10% of a thixotropic agent.
[0009] Optionally, the organic solvent is selected from one or more of 2-ethyl-1,3-hexanediol, 3-methyl-1,5-pentanediol, 2-hexyl-1-decanol, pentaerythritol, terpineol, benzyl alcohol, rosin amine polyoxyethylene ether, propylene glycol butyl ether, tripropylene glycol butyl ether, n-nonanol, 3-hexanol, undecanol, tetraethylene glycol, and propylene glycol.
[0010] Optionally, the rosin is selected from one or more of KE-604 rosin and KE-625 rosin.
[0011] Optionally, the active agent is selected from one or more of malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, itaconic acid, 2-ethylimidazole, phenylsuccinic acid, cyclohexylamine hydrochloride and diphenylguanidine hydrobromide, salicylic acid, oxalic acid, hexadecanoic acid, oxalic acid, maleic acid, 2-ethylhexanoic acid, tartaric acid, glycolic acid, and 2,2-hydroxymethylpropionic acid.
[0012] Optionally, the corrosion inhibitor is selected from one or more of benzotriazole, methylbenzotriazole and p-tert-butylcatechol.
[0013] Optionally, the thixotropic agent is selected from one of hydrogenated castor oil, polyamide wax 6650, and polyamide wax 6500.
[0014] Second aspect
[0015] The present invention provides a method for preparing a soldering flux, characterized in that it comprises the following steps:
[0016] The organic solvent, rosin, active agent and corrosion inhibitor are mixed and heated in a water bath for the first stirring to obtain a preliminary mixture;
[0017] adding a thixotropic agent to the preliminary mixture and performing a second stirring to obtain a flux matrix;
[0018] The soldering flux matrix is cooled to room temperature and then ground into powder to obtain the soldering flux.
[0019] Optionally, the temperature of the water bath is 85° C., the first stirring time is 30 min, and the second stirring time is 30 min.
[0020] Optionally, the flux matrix is ground to a particle size of less than 20 microns using a three-roll mill.
[0021] The third aspect
[0022] The present invention provides a solder paste, comprising solder powder and the soldering flux according to any one of claims 1 to 6;
[0023] The solder powder is selected from one of SnPb series, SnPbBi series, SnPbAg series, SnBiAg series, SnIn series, and SnAgCu series alloys.
[0024] The invention has the following beneficial effects: an organic solvent, rosin, an activator and a corrosion inhibitor are mixed, and heated in a water bath for a first stirring to obtain a preliminary mixture, a thixotropic agent is added to the preliminary mixture, and a second stirring is performed to obtain a soldering flux matrix; the soldering flux matrix is cooled to room temperature, and then ground into powder to obtain the soldering flux, and solder powder and the soldering flux are stirred to obtain the soldering flux; the solder paste provided by the invention does not diffuse after printing, and has very little residue after welding, and the residue does not diffuse, does not affect photovoltaic absorption efficiency, and is simple to prepare and has high welding efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0026] Figure 1 is a TGA test result diagram of the soldering flux of Example 1;
[0027] Figure 2 is a TGA test result diagram of the soldering flux of Example 2;
[0028] Figure 3 is a TGA test result diagram of the soldering flux of Example 3;
[0029] Figure 4 is a TGA test result diagram of the soldering flux of Example 4;
[0030] Figure 5 is a TGA test result diagram of the soldering flux of Example 5;
[0031] Figure 6 is a TGA test result diagram of the soldering flux of Example 6;
[0032] Figure 7 is a TGA test result diagram of the soldering flux of Example 7;
[0033] Figure 8 This is a TGA test result diagram of the soldering flux of Comparative Example 1;
[0034] Fig. 9 This is a TGA test result diagram of the soldering flux of Comparative Example 2.
[0035] Fig.10 This is a TGA test result diagram of the soldering flux of Comparative Example 3;
[0036] Fig.11It is a flow chart of the flux preparation method. DETAILED DESCRIPTION
[0037] The following will clearly and completely describe the concept, specific structure and technical effects of the present invention in combination with the embodiments and drawings, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. In addition, all the connection / connection relationships involved in the patent do not refer to the direct connection of components, but refer to the formation of a better connection structure by adding or reducing connection accessories according to the specific implementation situation. The various technical features in the invention can be combined interchangeably without conflicting with each other.
[0038] The solder paste used in existing welding technology has a high boiling point of solvents, activators and other components in the flux, which are not easy to volatilize during the welding process, resulting in a large amount of residue after welding. These residues will form protrusions and generate stress, and may also cause corrosion to the solder joints, causing the solder joints to detach or break, leading to failure.
[0039] The invention provides a soldering flux, which comprises, by mass percentage, 70-90% of an organic solvent, 2-10% of rosin, 2-30% of an activator, 0.50-2.50% of a corrosion inhibitor and 2-10% of a thixotropic agent.
[0040] The organic solvent is selected from one or more of 2-ethyl-1,3-hexanediol, 3-methyl-1,5-pentanediol, 2-hexyl-1-decanol, pentaerythritol, terpineol, benzyl alcohol, propylene glycol butyl ether, tripropylene glycol butyl ether, n-nonanol, 3-hexanol, undecanol, tetraethylene glycol, and propylene glycol.
[0041] The rosin is selected from one or more of KE-604 rosin and KE-625 rosin.
[0042] The active agent is selected from one or more of malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, itaconic acid, 2-ethylimidazole, phenylsuccinic acid, cyclohexylamine hydrochloride and diphenylguanidine hydrobromide, salicylic acid, oxalic acid, hexadecanoic acid, oxalic acid, maleic acid, 2-ethylhexanoic acid, tartaric acid, glycolic acid, and 2,2-hydroxymethylpropionic acid.
[0043] The corrosion inhibitor is selected from one or more of benzotriazole, methylbenzotriazole and p-tert-butylcatechol.
[0044] The thixotropic agent is selected from one of hydrogenated castor oil, polyamide wax 6650 and polyamide wax 6500.
[0045] The soldering flux provided by the present invention is prepared by the following method, and the specific steps are as follows:
[0046] S1, mixing an organic solvent, rosin, an active agent and a corrosion inhibitor, and heating in a water bath for a first stirring to obtain a preliminary mixture;
[0047] S2, adding thixotropic agent to the preliminary mixture, stirring for the second time, flux matrix;
[0048] S3, cooling the soldering flux matrix to room temperature, and grinding it into powder to obtain the soldering flux.
[0049] In the above steps, the temperature of the water bath is 85° C., the first stirring time is 30 minutes, the second stirring time is 30 minutes, and the flux matrix is ground to a particle size of less than 20 microns using a three-roll mill.
[0050] The present invention also provides a solder paste, comprising solder powder and the above soldering flux, wherein the solder powder is selected from one of SnPb, SnPbBi, SnPbAg, SnBiAg, SnIn, and SnAgCu alloys.
[0051] The solder paste provided by the invention is prepared by stirring solder powder and soldering flux.
[0052] Example 1
[0053] A solder paste is prepared by mixing and stirring 11% of soldering flux and 89% of solder powder, calculated by weight percentage.
[0054] The solder powder is Sn63Pb37 alloy T4 (20-38 μm).
[0055] Among them, the flux is composed of the following components by mass percentage:
[0056]
[0057] 3-methyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, KE-604 rosin, 2-ethylimidazole, succinic acid, itaconic acid, diphenylguanidine hydrobromide, and benzotriazole were mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; polyamide wax 6650 was then added, and stirring was continued for 30 minutes to obtain a flux matrix; after the flux matrix was cooled to room temperature, it was ground with a three-roll mill to less than 20 microns to obtain a flux.
[0058] Example 2
[0059] A solder paste is prepared by mixing and stirring 12% of soldering flux and 88% of solder powder, calculated by weight percentage.
[0060] The solder powder is Sn63Pb37 alloy T5 (15-25 μm).
[0061] Among them, the flux is composed of the following components by mass percentage:
[0062]
[0063]
[0064] 3-methyl-1,5-pentanediol, rosin amine polyoxyethylene ether, KE-625 rosin, 2-ethylimidazole, phenylsuccinic acid, malonic acid, cyclohexylamine hydrochloride, benzotriazole and methylbenzotriazole are mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; hydrogenated castor oil is then added, and stirring is continued for 30 minutes to obtain a flux matrix; after the flux matrix is cooled to room temperature, it is ground with a three-roll mill to less than 20 microns to obtain a flux.
[0065] Example 3
[0066] A solder paste is prepared by mixing and stirring 11% of soldering flux and 89% of solder powder, calculated by weight percentage.
[0067] The solder powder is Sn43Pb43Bi 14 alloy T4 (20-38 μm).
[0068] Among them, the flux is composed of the following components by mass percentage:
[0069]
[0070]
[0071] Tripropylene glycol butyl ether, KE-604 rosin, 2-ethylimidazole, sebacic acid, adipic acid, diphenylguanidine hydrobromide, benzotriazole and methylbenzotriazole are mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; polyamide wax 6650 is then added, and stirring is continued for 30 minutes to obtain a flux matrix; after the flux matrix is cooled to room temperature, it is ground with a three-roll mill to less than 20 microns to obtain a flux.
[0072] Example 4
[0073] A solder paste is prepared by mixing and stirring 11% of soldering flux and 89% of solder powder, calculated by weight percentage.
[0074] Among them, the solder powder is Sn62.8Pb36.8Ag0.4 alloy T4 (20-38μm).
[0075] Among them, the flux is composed of the following components by mass percentage:
[0076]
[0077] 3-methyl-1,5-pentanediol, rosin amine polyoxyethylene ether, KE-604 rosin, 2-ethylimidazole, succinic acid, malonic acid, cyclohexylamine hydrochloride and benzotriazole were mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; polyamide wax 6650 was then added, and stirring was continued for 30 minutes to obtain a flux matrix; after the flux matrix was cooled to room temperature, it was ground with a three-roll mill to less than 20 microns to obtain a flux.
[0078] Example 5
[0079] A solder paste is prepared by mixing and stirring 15% of soldering flux and 85% of solder powder, calculated by weight percentage.
[0080] The solder powder is Sn96.5Ag3Cu0.5 alloy T6 (5-15 μm).
[0081] Among them, the flux is composed of the following components by mass percentage:
[0082]
[0083] Tripropylene glycol butyl ether, KE-604 rosin, 2-ethylimidazole, succinic acid, phenylsuccinic acid, diphenylguanidine hydrobromide, and methylbenzotriazole are mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; hydrogenated castor oil is then added, and stirring is continued for 30 minutes to obtain a flux matrix; after the flux matrix is cooled to room temperature, it is ground with a three-roll mill to less than 20 microns to obtain a flux.
[0084] Example 6
[0085] A solder paste is prepared by mixing and stirring 11% of soldering flux and 89% of solder powder, calculated by weight percentage.
[0086] The solder powder is Sn63Pb37 alloy T4 (20-38 μm).
[0087] Among them, the flux is composed of the following components by mass percentage:
[0088]
[0089] 2-ethyl-1,3-hexanediol, propylene glycol, n-nonanol, KE-604 rosin, adipic acid, 2,2-hydroxymethylpropionic acid, cyclohexylamine hydrochloride and methylbenzotriazole are mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; hydrogenated castor oil is then added, and stirring is continued for 30 minutes to obtain a flux matrix; after the flux matrix is cooled to room temperature, it is ground with a three-roll mill to less than 20 microns to obtain a flux.
[0090] Example 7
[0091] A solder paste is prepared by mixing and stirring 11% of soldering flux and 89% of solder powder, calculated by weight percentage.
[0092] The solder powder is Sn63Pb37 alloy T4 (20-38 μm).
[0093] Among them, the flux is composed of the following components by mass percentage:
[0094]
[0095]
[0096] Tripropylene glycol butyl ether, propylene glycol, n-nonanol, KE-625 rosin, maleic acid, 2,2-hydroxymethylpropionic acid, diphenylguanidine hydrobromide and benzotriazole are mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; polyamide wax 6650 is then added, and stirring is continued for 30 minutes to obtain a flux matrix; after the flux matrix is cooled to room temperature, it is ground with a three-roll mill to less than 20 microns to obtain a flux.
[0097] Comparative Example 1
[0098] A solder paste is prepared by mixing and stirring 11% of soldering flux and 89% of solder powder, calculated by weight percentage.
[0099] The solder powder is Sn63Pb37 alloy T4 (20-38 μm).
[0100] Among them, the flux is composed of the following components by mass percentage:
[0101]
[0102]
[0103] 3-methyl-1,5-pentanediol, KE-625 rosin, 2-ethylimidazole, phenylsuccinic acid, malonic acid, adipic acid, diphenylguanidine hydrobromide, benzotriazole and methylbenzotriazole were mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; polyamide wax 6650 was then added, and stirring was continued for 30 minutes to obtain a flux matrix; after the flux matrix was cooled to room temperature, it was ground with a three-roll mill to less than 20 microns to obtain a flux.
[0104] Comparative Example 2
[0105] A solder paste is prepared by mixing and stirring 12% of soldering flux and 88% of solder powder, calculated by weight percentage.
[0106] The solder powder is Sn63Pb37 alloy T5 (15-25 μm).
[0107] Among them, the flux is composed of the following components by mass percentage:
[0108]
[0109] Tripropylene glycol butyl ether, KE-604 rosin, 2-ethylimidazole, succinic acid, sebacic acid, diphenylguanidine hydrobromide, benzotriazole and methylbenzotriazole are mixed in the above proportions, heated and stirred in a water bath at 85°C for 30 minutes to obtain a preliminary mixture; hydrogenated castor oil is then added, and stirring is continued for 30 minutes to obtain a flux matrix; after the flux matrix is cooled to room temperature, it is ground with a three-roll mill to less than 20 microns to obtain a flux.
[0110] Comparative Example 3
[0111] A solder paste is prepared by mixing and stirring 12% of flux and 88% of solder powder of the same solder paste available on the market, calculated by weight percentage.
[0112] The solder powder is Sn63Pb37 alloy T4 (20-38 μm).
[0113] The flux TGA test, solder paste solder joint test, flux residue test and residue diffusion test were performed on Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2, 3 respectively, and the test methods are as follows:
[0114] Flux TGA test: NETZSCH TG209F3, heating range 30~300℃, heating rate 30℃ / min, calculate the flux weight loss.
[0115] Solder paste solder joint test: The above solder paste was printed on the copper sheet with a steel mesh, the heating table temperature was set to 270°C, the copper sheet was placed on the heating table for heating, the heating time was 5 seconds, and the appearance of the solder joint was observed under a microscope. The above solder paste was printed on the photovoltaic Si substrate with a steel mesh, the electric heating table was set to 270°C, the copper sheet was placed on the heating table for heating, the heating time was 5 seconds, and the appearance of the solder joint was observed under a microscope.
[0116] Flux residue test: Print solder paste on a copper sheet using a 0.1mm steel mesh, set the heating table temperature to 270°C, and heat the copper sheet on the heating table for 5 seconds. Calculate the flux residue based on the amount of solder paste printed and the weight after heating.
[0117] Residue diffusion test: The solder paste is printed on the silicon wafer using a steel screen with a thickness of 0.1mm and an opening length of 10.000mm. The heating table is heated at 270℃ for 5 seconds, and the total length of the residue after diffusion is measured.
[0118] The test results are as follows:
[0119] The soldering flux TGA test of Example 1: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 1 The test results show that the weight loss is 87.02% when the temperature rises from 30 to 300°C.
[0120] The solder paste solder joint test of Example 1 shows that the solder joints on the copper sheet are bright and full, with little flux residue, and the residual flux is 1.4278%. There is no diffusion of solder joints on the photovoltaic substrate, that is, no "over-soldering" phenomenon.
[0121] The total length of the residue of Example 1 after diffusion is 11.420 mm.
[0122] The soldering flux TGA test of Example 2: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 2 The results showed that the weight loss was 85.60% when the temperature was increased from 30 to 300°C.
[0123] The solder paste solder joint test of Example 2: The results show that the solder joints on the copper sheet are bright and full, with little flux residue, and the residual flux is 1.728%. There is no diffusion of the solder joints on the photovoltaic substrate, that is, no "over-soldering" phenomenon.
[0124] The total length of the residue of Example 2 after diffusion is 11.416 mm.
[0125] The soldering flux TGA test of Example 3: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 3 The test results show that the weight loss is 90.17% when the temperature rises from 30 to 300°C.
[0126] The solder paste solder joint test of Example 3 shows that the solder joints on the copper sheet are bright and full, with little flux residue, and the residual flux is 1.0813%. There is no diffusion of solder joints on the photovoltaic substrate, that is, no "over-soldering" phenomenon.
[0127] The total length of the residue of Example 3 after diffusion is 11.642 mm.
[0128] The soldering flux TGA test of Example 4: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 4 The test results show that the weight loss is 88.34% when the temperature rises from 30 to 300°C.
[0129] The solder paste solder joint test of Example 4 shows that the solder joints on the copper sheet are bright and full, with little flux residue, and the residual flux is 1.2826%. There is no diffusion of solder joints on the photovoltaic substrate, that is, no "over-soldering" phenomenon.
[0130] The total length of the residue of Example 4 after diffusion is 11.285 mm.
[0131] The soldering flux TGA test of Example 5: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 5 The results showed that the weight loss was 87.95% when the temperature was increased from 30 to 300°C.
[0132] The solder paste solder joint test of Example 5 shows that the solder joints on the copper sheet are bright and full, with little flux residue, and the residual flux is 1.8075%. There is no diffusion of solder joints on the photovoltaic substrate, that is, no "over-soldering" phenomenon.
[0133] The total length of the residue of Example 5 after diffusion is 11.347 mm.
[0134] The soldering flux TGA test of Example 6: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 6 The results showed that the weight loss was 92.63% when the temperature was increased from 30 to 300°C.
[0135] The solder paste solder joint test of Example 6 shows that the solder joints on the copper sheet are bright and full, with little flux residue, and the residual flux is 0.8107%. There is no diffusion of solder joints on the photovoltaic substrate, that is, no "over-soldering" phenomenon.
[0136] The total length of the residue of Example 6 after diffusion is 11.29 mm.
[0137] The soldering flux TGA test of Example 7: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 7 The results showed that the weight loss was 93.54% when the temperature was increased from 30 to 300°C.
[0138] The solder paste solder joint test of Example 7 shows that the solder joints on the copper sheet are bright and full, with little flux residue, and the residual flux is 0.7106%. There is no diffusion of solder joints on the photovoltaic substrate, that is, no "over-soldering" phenomenon.
[0139] The total length of the residue of Example 7 after diffusion was 11.35 mm.
[0140] TGA test of soldering flux in comparative example 1: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 6 The test results show that the weight loss is 64.79% when the temperature rises from 30 to 300°C.
[0141] The solder paste solder joint test of comparative example 1: The results show that the solder joints on the copper sheet are bright, and there is a lot of flux residue, with a flux residue of 3.8181%. There is diffusion of solder joints on the photovoltaic substrate, that is, there is a phenomenon of "over-soldering".
[0142] The total length of the residue of Comparative Example 1 after diffusion was 12.585 mm.
[0143] TGA test of soldering flux in comparative example 2: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 7 The test results show that the weight loss is 49.43% when the temperature rises from 30 to 300°C.
[0144] The solder paste solder joint test of comparative example 2: The results show that the solder joints on the copper sheet are bright, with a lot of flux residue, and the residual flux is 6.084%. There is diffusion of solder joints on the photovoltaic substrate, that is, there is a phenomenon of "over-soldering".
[0145] The total length of the residue of Comparative Example 2 after diffusion was 14.260 mm.
[0146] Comparative Example 3 Soldering Flux TGA Test: The soldering flux was tested using a thermogravimetric analyzer, such as Figure 8 The test results show that the weight loss is 65.29% when the temperature rises from 30 to 300°C.
[0147] The solder paste solder joint test of comparative example 3: The results show that the solder joints on the copper sheet are bright, with a lot of flux residue, and the flux residue is 4.2252%. There is diffusion of solder joints on the photovoltaic substrate, that is, there is a phenomenon of "over-soldering".
[0148] The total length of the residue of Comparative Example 3 after diffusion was 14.170 mm.
[0149] The test results of flux and solder paste are summarized in the following table:
[0150]
[0151]
[0152] The flux provided by the present invention has a weight loss of more than 85% at 30-300°C in a flux TGA test, which means that it is easy to volatilize during the welding process, and will not generate a large amount of residue during the welding process, thereby ensuring the stability of the solder joints; and the solder paste provided by the present invention has bright and full solder joints on the copper sheet in the solder paste solder joint test results, and there is diffusion of solder joints on the photovoltaic substrate, that is, there is an "over-soldering" phenomenon, and there is little flux residue, which means that the solder paste provided by the present invention will not cause the failure of the silver plating layer of the substrate on the photovoltaic substrate due to the transition wetting reaction of the solder, and will not generate a large amount of residue during welding, thereby ensuring the welding stability and photoelectric conversion efficiency, and the solder paste welding efficiency is higher than that of copper wire welding, and the solder paste composed of solder powder and flux is simpler than the preparation process of the solder paste filled with gas, so the generation efficiency is also higher.
[0153] The above is a specific description of the preferred implementation of the present invention, but the invention is not limited to the embodiments. Those skilled in the art can make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A soldering flux, characterized in that: The composition comprises, by mass percentage, 70-90% of an organic solvent, 2-10% of rosin, 2-10% of an activator, 0.50-2.50% of a corrosion inhibitor and 2-10% of a thixotropic agent.
2. The soldering flux according to claim 1, characterized in that The organic solvent is selected from one or more of 2-ethyl-1,3-hexanediol, 3-methyl-1,5-pentanediol, 2-hexyl-1-decanol, pentaerythritol, terpineol, benzyl alcohol, rosin amine polyoxyethylene ether, propylene glycol butyl ether, tripropylene glycol butyl ether, n-nonanol, 3-hexanol, undecanol, tetraethylene glycol, and propylene glycol.
3. The soldering flux according to claim 1, characterized in that The rosin is selected from one or more of KE-604 rosin and KE-625 rosin.
4. The soldering flux according to claim 1, characterized in that The active agent is selected from one or more of malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, itaconic acid, 2-ethylimidazole, phenylsuccinic acid, cyclohexylamine hydrochloride and diphenylguanidine hydrobromide, salicylic acid, oxalic acid, hexadecanoic acid, oxalic acid, maleic acid, 2-ethylhexanoic acid, tartaric acid, glycolic acid, and 2,2-hydroxymethylpropionic acid.
5. The soldering flux according to claim 1, characterized in that The corrosion inhibitor is selected from one or more of benzotriazole, methylbenzotriazole and p-tert-butylcatechol.
6. The soldering flux according to claim 1, characterized in that The thixotropic agent is selected from one of hydrogenated castor oil, polyamide wax 6650 and polyamide wax 6500.
7. A method for preparing the soldering flux according to any one of claims 1 to 6, characterized in that: The following steps are involved: The organic solvent, rosin, active agent and corrosion inhibitor are mixed and heated in a water bath for the first stirring to obtain a preliminary mixture; adding a thixotropic agent to the preliminary mixture and performing a second stirring to obtain a flux matrix; The soldering flux matrix is cooled to room temperature and then ground into powder to obtain the soldering flux.
8. The preparation method according to claim 7, characterized in that: The temperature of the water bath was 85° C., the first stirring time was 30 min, and the second stirring time was 30 min.
9. The preparation method according to claim 7, characterized in that: The flux matrix is ground to a particle size of less than 20 microns using a three-roll mill.
10. A solder paste, characterized in that: Comprising solder powder and the soldering flux according to any one of claims 1 to 6; The solder powder is selected from one of SnPb series, SnPbBi series, SnPbAg series, SnBiAg series, SnIn series, and SnAgCu series alloys.